The future of wearable technology for game analysis - Abt, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Although `wearable` technology has been around for decades (Polar Innovations, n.d.), only recently has the combination of adequate battery power, pervasive wireless networks, and miniaturisation of electronic components, allowed wearable technology to reach mainstream use. The current poster-child of wearable technology for game analysis is the Global Positioning System (GPS). GPS provides coaches and sport scientists with information on player location and its derivatives - speed and direction. Current GPS systems also include heart rate monitoring, together with triaxial accelerometers and gyroscopes, which are increasingly being used to measure rapid changes in direction and speed (Aughey, 2011). Despite wide adoption of GPS, we have only just begun to explore the potential of wearable technology for game analysis. For example, we now have the capability to measure a wider range of physiological data, including temperature, hydration status, heart rate variability, and even blood lactate. These measures can be obtained through new methods of data acquisition such as flexible skin-mounted sensors (MC10, n.d.), electronic circuits sewn into fabric (OMsignal, n.d.), electromyography (Leo, n.d.), or near-infrared spectroscopy (BSX Insight, n.d.). All of this data is available in real-time and connected to the cloud for storage and sharing via wireless networks. Vast amounts of data collected from this array of wearable technology will increasingly allow the use of multivariate approaches to analysis as used in machine learning and data mining. However, it will be the fusion of these data (Weaving et al., 2014; Liu et al., 2012) that will provide unique insights into not only the stress placed on players during training and competition, but also the interactions between the physical, technical, and tactical aspects of a game.